The effects of dose of flupentixol decanoate on relapse rates in schizophrenia - Reed, P; Fanshawe, T (2011)
Aims and method: To systematically review the published literature with respect to formulating a dose-response curve for flupentixol decanoate. A systematic literature search using the Cochrane Database was performed for studies that published both dosage information and data on relapse rates. Results: The data showed modest effects of dose on survival rates. Increasing dose may be associated with increased survival rates up to around 50-60 mg of flupentixol decanoate every 4 weeks. There was no evidence of increased survival rates at higher doses and higher doses may be associated with lower rates of survival. There is considerable uncertainty as to the true effects of dose of flupentixol decanoate on relapse rates. Clinical implications: There is no evidence that survival rates improve for doses above 50-60 mg every 4 weeks. These doses are much lower than doses commonly prescribed. Clinicians may wish to consider these data when prescribing flupentixol decanoate. Declaration of interest: None.